The effect of extracorporeal membrane oxygenation on neurodevelopmental outcomes in children after repair of congenital heart disease: A pilot study from Turkey - Basgoze, Serdar; Temur, Bahar; Ozcan, Zeynep Sila; Gokce, Ibrahim; Guvenc, Osman; Aydin, Selim; Guzelmeric, Fusun; Altan Kus, Aylin; Erek, Ersin (Frontiers in Pediatrics, 2023)
Background Extracorporeal membrane oxygenation (ECMO) is widely used after congenital heart surgery. The purpose of this study is to analyze the neurodevelopmental (ND) outcomes in patients who require ECMO support after congenital cardiac surgery. Methods Between January 2014 and January 2021, 111 patients (5.8%) required ECMO support after congenital heart operations, and 29 of these patients were discharged. Fifteen patients who met the inclusion criteria were included. A propensity score matching (PSM) analysis model was established using eight variables (age, weight, sex, Modified Aristotle Comprehensive Complexity scores, seizures, cardiopulmonary bypass duration, number of operations, and repair method) with 1:1 matching. According to the PSM model, 15 patients who underwent congenital heart operations were selected as the non-ECMO group. The Ages & Stages Questionnaire Third Edition (ASQ-3) was used for ND screening; it includes communication, physical skills (gross and fine motor), problem-solving, and personal–social skills domains. Results There were no statistically significant differences between the patients’ preoperative and postoperative characteristics. All patients were followed up for a median of 36 months (10–60 months). The ASQ-3 results revealed that communication, fine motor, and personal–social skills assessments were not statistically significant between the groups. Gross motor skills, problem-solving skills, and overall scores were better in the non-ECMO patients (P = 0.01, P = 0.03, and P = 0.03, respectively). Conclusion ND delay may occur in congenital heart surgery patients who require ECMO support. We recommend ND screening in all patients with congenital heart disease, especially those who need ECMO support.